Optimalisasi Pelaksanaan Program KALIMASADA dalam Pendampingan Layanan Administrasi Kependudukan di Kelurahan Nginden Jangkungan Surabaya - Lestari, Amelia Dwi; Dwiridotjahjono, Jojok (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article will discuss the role of students in carrying out assistance in population administration services through optimizing the implementation of the KALIMASADA Program in the Surabaya City Population and Civil Registration Service, especially in the Nginden Jangkungan Subdistrict area, Surabaya. This program aims to increase public literacy regarding the importance of population administration, provide direct assistance to the community and optimize Population Administration services in Nginden Jangkungan Village. The method used in the population administration services assistance program is a participatory approach with descriptive methods. A participatory approach is an approach that formulates regional or village development needs that prioritize the community. Students carry out field trip surveys directly to the community. The results of this mentoring program show that the role of students in assisting with population administration services really helps the community in fulfilling population administration documents. This assistance activity can help the community understand the importance of population administration documents and fulfill population administration documents.